Spolupráca škôl a podnikov v rámci duálneho systému vzdelávania - Strižencová, Michaela (Univerzita Pardubice, 1999)
The Dual System of Vocational Education has a long tradition in Switzerland as well as in Germany and Austria. Most typical characteristic of this system is that the teachinglearning processes take place simultaneously in an enterprise and at school. The Dual System has its strengths (low youth unemployment, practice-oriented, motivating, possibilities for career advancement) as well as its weaknesses (not equivalent to general education, extremely complex).
Keywords: Vzdělávání; vzdělávací systémy; školy; podniky; Spolupráce